PENDIDIKAN ISLAM DALAM PERSPEKTIF WORLD CONVERENCE ON MUSLIM EDUCATION: TELAAH ONTOLOGIS, AKSIOLOGIS, DAN EPISTEMOLOGIS - Salminawati, Salminawati; Usiono, Usiono; Ananda, Fauzi (Jurnal Bilqolam Pendidikan Islam, 2024)
The decline in science is due to the western world having mastered all aspects of science so that the Muslim world is left behind. The arrival of Western secularism which dominates science with its modern style, has given rise to concerns for Muslim thinkers. This problem formed the basis for the formation of the world Islamic education conference. This research aims to explain the study of ontology, epistemology and axiology of Islamic education from the perspective of the world Islamic education conference. The method used in this writing is library research. The results obtained are that this world Islamic education seminar has no set time, this seminar can be held at any time in accordance with the agreement, there is no difference between general knowledge and religion and there is an integration of science